As Good as the Company They Keep? : Improving Farmers’ Social Networks - Leonard, Kenneth (World Bank, Washington, DC, 2016)
Extension services have a history of being relatively expensive and not always effective. At the same time, studies show that informal social networks can be very beneficial in helping increase productivity. In Uganda, the authors tested the value of informal social networks for women farmers by connecting the least-productive 30 percent to some of the most productive women farmers in their own villages. Results show significant gains in productivity indicating that the path to better outcomes is contained within their own community. Women learned the agricultural information at least as well in a network setting as in a more intensive, formal extension setting. On average, the social network intervention was less costly and more effectively targeted women and the least productive farmers than traditional extension services. By exploiting the power of social ties, social network interventions offer a lower-cost alternative to traditional agricultural training programs and can be particularly effective at improving the productivity of women. The results of the study featured in this brief are particularly relevant to policymakers in Sub-Saharan Africa, where productivity differentials still exist between males and females, and women are less frequently targeted for training.